Creep Rapture of Structures at Elevated Temperature and Estimates of Rupture Life - Wojewódzki, W. (Engineering Transactions, 1978)
A description of creep rupture at elevated temperature is proposed. The functions introduced to the constitutive equations were determined from the results of technically possible experiments in the uniaxial stress state. The description is shown to be useful in an investigation of the influence of the elevated temperature, the temperature gradients, its cyclic fluctuations and the cyclic proportional loading upon the stress redistribution, the amount of deformation, the propagation of the damage front and the rupture life of structures. Using the methods for bounding the rupture life of structures, the lower and upper bounds for simple structures were also obtained and compared with the given exact solution.